Formation of ZnO Micro-Flowers Prepared via Solution Process and their Antibacterial Activity - Mishra Amrita; Yun Soon-Il; Wahab Rizwan; Kim Young-Soon; Shin Hyung-Shik (Nanoscale Research Letters, 2010)
Abstract This paper presents the fabrication and characterization of zinc oxide micro-flowers and their antibacterial activity. The micro-flowers of zinc oxide composed of hexagonal nanorods have been prepared via solution process using precursor zinc acetate di-hydrate and sodium hydroxide in 3 h of refluxing time at ~90°C. The antibacterial activities of grown micro-flowers were investigated against four pathogenic bacteria namely S. aureus, E. coli, S. typhimurium and K. pneumoniae by taking five different concentrations (5–45 μg/ml) of ZnO micro-flowers (ZnO-MFs). Our investigation reveals that at lowest concentration of ZnO-MFs solution inhibiting the growth of microbial strain which was found to be 5 μg/ml for all the tested pathogens. Additionally, on the basis of morphological and chemical observations, a chemical reaction mechanism of ZnO-MFs composed of hexagonal nanorods was also proposed.